Constructions with parataxis and homogeneous parts in poetical text - Дарчук, Наталія Петрівна (Київський національний університет імені Тараса Шевченка, 2020)
The work considers peculiarities in conducting of automated syntactic analysis (ASA) on basis of poetical texts and as result studying the features of linear structure of Ukrainian texts, in particular, texts with constructions with parataxis and homogeneous parts. The process of text analysis includes two stages: the first stage starts with automated syntactic analysis of hierarchical structure of text, which finally builds a dependency tree. On the second stage the graph received as result of automated analysis specifies information on type or model of a sentence, in particular, with available constructions with parataxis homogeneous parts. The purpose of the work from linguistic standpoint is the analysis of parataxis/homogeneous parts in poetical texts and their relations to the content. The study of texts (1600 sentences) showed that constructions with parataxis can build three groups of relations with: homogenous parts, non-homogenous and a combination of both parts. Analysis of constructions with parataxis with available dominating syntactical level demonstrated specific features of poetical structure of texts of four analyzed authors Vinhranovskyi, Drach, Moisiienko and Stus. Project follow-up is viewed in the study of correlation between syntactical and semantic analysis of text structures, since the form of poetical text specifies of how the poetical language is shaped in sense of qualitative features. Study of construction with parataxis within both a single author’s style and an array of other authors’ styles presents interest and future prospects from the standpoint of carrying qualitative semantic analysis of parataxis with available homogenous items. It is possible since all variants of lexical meaning in the Corpora (their number reaches over 120 K) are automatically marked with special codes of taxonomic classification and with code showing relation to some or other taxon. This technology makes possible to conduct a comprehensive analysis of constructions with parataxis, to create lists and sort out relations of such type of constructions within the range of a dependency tree to detect and identify common and miscellaneous features in the structure of parataxis as a parameter of an individual writing style of a single author.

Дослідження пов’язане з побудовою автоматичного синтаксичного аналізу (АСА) поетичних текстів і, як наслідок, – вивченням властивостей лінійної структури українськомовного тексту, а саме – конструкцій із перерахуванням (КП). Процес аналізу двоетапний: на першому етапі працює автоматичний синтаксичний аналіз ієрархічного типу, який завершується побудовою дерева залежностей (ДЗ), а на другому – з одержаного графа автоматично здобувається інформація про модель речення, зокрема про наявність КП, які є частиною сурядних конструкцій. Метою дослідження з лінгвістичної точки зору є аналіз на змістовому рівні КП, а саме набір сурядних та однорідних членів та різний їх розподіл.
Конструкції з сурядністю / однорідністю в поетичних текстах
Keywords: автоматичний синтаксичний аналіз; дерево залежностей; конструкції з перерахуванням; сурядні та однорідні члени речення; automated syntactic analysis; dependency tree; structures with parataxis